Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV METEOR during cruise M196 - Jegen, Marion; Pandolpho, Bruna; Schumacher, Mia (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M196 using a Kongsberg EM 710 multibeam echosounder. The expedition took place during 05.12.2023 - 27.12.2023 from Piraeus (Greece) to Limassol (Cyprus) in the Mediterranean Sea. The major aim of M196 was to investigate a newly-discovered OFG (offshore freshened groundwater) site within the Gulf of Corinth, Greece. Data were recorded in the EEZ of Greece. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam